Post-COVID-19 syndrome in patients with primary Sjogren's syndrome after acute SARS-CoV-2 infection - İNANÇ, GÜZİDE NEVSUN (My University, 2021)
Objective. To analyse the frequency and characteristics of post-COVID-19 syndrome in patients with primary Sjogren\"s syndrome (pSS) affected by acute SARS-CoV-2 infection.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; primary Sjogren syndrome; post-COVID-19 syndrome; SARS-CoV-2; long COVID-19; hydroxychloroquine; hospital admission; CLASSIFICATION CRITERIA; COVID-19; CONSENSUS